The Relationship between Mathematical Curiosity and Mathematical Learning Motivation on Computational - Fitrianingsih, Noviana; Fakhriyana, Dina (Universitas Islam Negeri Sunan Kudus, 2025)
Various affective factors can influence the extent to which students' computational thinking ability develop. Among them are students’ curiosity and learning motivation when studying mathematics. This study aims to determine the relationship between mathematical curiosity and mathematical learning motivation with computational thinking ability. This research is a type of correlational study with a quantitative approach. The research was conducted in class VIII at a school in the Bae, Kudus, with a total sample of 34 students. The data in this study were collected through a questionnaire of mathematical curiosity and mathematical learning motivation, a computational thinking ability test, and observations. Meanwhile, the data were analyzed using simple and multiple linear regression. The results of this study show that 1) Mathematical curiosity has a positive and significant relationship with computational thinking ability with a strong correlation coefficient of 0.770; 2) Mathematical learning motivation has a positive and significant relationship with computational thinking ability with a strong correlation coefficient of 0.771; 3) Mathematical curiosity and mathematical learning motivation had a positive and significant relationship with computational thinking ability with a very strong correlation coefficient of 0.803. This research is expected to be a reference for further studies on the role of psychological factors in shaping computational thinking skills, by showing the relationship between mathematical curiosity and motivation to learn mathematics to computational thinking ability in solving problems in one-variable linear equation material. Practically, the results of this study can help teachers to design mathematics instruction that fosters students' curiosity and learning motivation to improve computational thinking ability.Keywords: Computational Thinking Ability; Mathematical Curiosity; Mathematical Learning Motivation Banyak aspek afektif yang dapat mempengaruhi sejauh mana kemampuan computational thinking peserta didik berkembang. Diantaranya yaitu curiosity serta learning motivation yang dimiliki peserta didik dalam pembelajaran matematika. Penelitian ini bertujuan untuk mengetahui hubungan antara mathematical curiosity dan mathematical learning motivation terhadap kemampuan computational thinking. Penelitian ini merupakan jenis penelitian korelasional dengan pendekatan kuantitatif. Penelitian dilaksanakan di kelas VIII salah satu madrasah di daerah Bae, Kudus, dengan sampel jenuh sebanyak 34 peserta didik. Data dalam penelitian ini diperoleh melalui angket mathematical curiosity dan mathematical learning motivation, tes kemampuan computational thinking, serta observasi. Sedangkan analisis data menggunakan regresi linear sederhana dan berganda. Hasil penelitian ini menunjukkan bahwa 1) Mathematical curiosity memiliki hubungan positif dan signifikan dengan kemampuan computational thinking dengan interpretasi hubungan yang kuat sebesar 0,770; 2) Mathematical learning motivation memiliki hubungan positif dan signifikan dengan kemampuan computational thinking dengan interpretasi hubungan yang kuat sebesar 0,771; 3) Mathematical curiosity dan mathematical learning motivation memiliki hubungan positif dan signifikan dengan kemampuan computational thinking dengan interpretasi hubungan yang sangat kuat sebesar 0,803. Penelitian ini diharapkan menjadi referensi bagi studi lanjutan mengenai peran faktor psikologis dalam membentuk kemampuan computational thinking, dengan menunjukkan hubungan antara mathematical curiosity dan mathematical learning motivation terhadap kemampuan computational thinking dalam menyelesaikan masalah pada materi persamaan linear satu variabel. Secara praktis, hasil penelitian ini dapat membantu guru untuk merancang pembelajaran matematika yang mendorong curiosity dan learning motivation peserta didik guna meningkatkan kemampuan computational thinking.Kata Kunci: Kemampuan Computational Thinking; Mathematical Curiosity; Mathematical Learning Motivation